U-Shaped Relationship Between MSpO2 Levels and the Incidence of Frailty in Elderly OSA Patients: Findings from a Multicenter Cohort Study [Letter] - Zhu H; Dong L (Clinical Interventions in Aging)
Hanqin Zhu, Lei Dong The second Affiliated Hospital of Zhejiang Chinese Medical University (Xinhua Hospital of Zhejiang Province), Hangzhou, Zhejiang, 310000, People’s Republic of ChinaCorrespondence: Lei Dong, The second Affiliated Hospital of Zhejiang Chinese Medical University (Xinhua Hospital of Zhejiang Province), No. 318, Chaowang Road, Gongshu District, Hangzhou, Zhejiang, People’s Republic of China, 310000, Email ramelei.1024@163.com